Промисли українців села Благодатне Донецької області - Максим, В. (Народна творчість та етнографія, 2007)
Pottery handcraft in Blagodatne village in Amvrosiyivsky region at the beginning of the 20th century. Solodovnyk Hryhoriy, Bilostotsky Kuzma and his son Petro were the founders of Center of Pottery. Methods of making ceramic plates and their assortment are described in the article.